2018
DOI: 10.1111/azo.12286
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the unique mudskipper Periophthalmodon septemradiatus living from estuary to upstream of the Hau River

Abstract: This study provided new knowledge on reproductive traits of the unique mudskipper Periophthalmodon septemradiatus that is also a potential aquarium pet. Fish specimens were obtained by using fishing rods at the muddy flat in tributaries of the Hau River from August 2017 to July 2018. Data analysis of a collection of 1,504 individuals (930 males and 674 females) showed that the sex ratio of this species was significantly different from the ratio 1:1. As mature gonads were found monthly during the study period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 32 publications
(59 reference statements)
1
35
0
2
Order By: Relevance
“…The collected specimens were preserved in 5.0% formalin and classified based on their external morphology according to the report of Tran et al (2013) in the laboratory. The fish sexes were differentiated based on the morphology of urogenital papilla, e.g., round in females and narrow in males (Dinh et al, 2020). In the zoological laboratory, B. koilomatodon specimens were measured for total length (nearest 0.1cm) and weighted (nearest 0.01g).…”
Section: Fish Collectionmentioning
confidence: 99%
“…The collected specimens were preserved in 5.0% formalin and classified based on their external morphology according to the report of Tran et al (2013) in the laboratory. The fish sexes were differentiated based on the morphology of urogenital papilla, e.g., round in females and narrow in males (Dinh et al, 2020). In the zoological laboratory, B. koilomatodon specimens were measured for total length (nearest 0.1cm) and weighted (nearest 0.01g).…”
Section: Fish Collectionmentioning
confidence: 99%
“…Tinh trùng thấy rõ là các tế bào nhỏ có đuôi với phần đầu chứa nhân bắt màu đậm hơn (Hình 3d). Sự phát triển tinh sào ở cá bống cát trải qua các giai đoạn có sự phát triển gần như tương đồng với các loài như: cá kèo vảy to Parapocryptes serpersater [10], cá bống sao Boleophthalmus boddarti [13], và cá bống trân Butis butis [14], cá bống trứng Eleotris melanosoma [15], cá bống mít Stigmatogobius pleurostigma [16] và cá thòi lòi Periophthalmodon septemradiatus [17]. Ở giai đoạn I, hình thái ngoài gần như giống nhau ở các loài các nêu trên, với tinh sào đều mảnh, nhỏ, dẹp, nằm sát vào cột sống của cá.…”
Section: Ghi Chú: T: Tổng Mẫu Cá Thu đượC Gđ1 Gđ2 Gđ 3 Và Gđ 4 Lầnunclassified
“…indicated that semelparity and iteroparity are two main reproductive strategies. Iteroparous is found in most gobiid species (Miller, 1984;Dinh et al, 2016;Dinh et al, 2020). There is a strong relationship between the strategy of reproduction and fishery (Miller, 1984;Komolafe and Arawomo, 2007;Dinh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Iteroparous is found in most gobiid species (Miller, 1984;Dinh et al, 2016;Dinh et al, 2020). There is a strong relationship between the strategy of reproduction and fishery (Miller, 1984;Komolafe and Arawomo, 2007;Dinh et al, 2020). Fontoura et al (2009) and Teichert et al (2014) noted that the information about body size when fish was mature firstly and batch fecundity played a vital role in managing the fish stock.…”
Section: Introductionmentioning
confidence: 99%